2021
DOI: 10.1177/00333549211029965
|View full text |Cite
|
Sign up to set email alerts
|

Loneliness Among US Adults Aged ≥55 Early in the COVID-19 Pandemic

Abstract: Objectives Loneliness is associated with increased risks of adverse health outcomes among middle-aged and older adults. We estimated the prevalence of loneliness and identified key sociodemographic, employment, living, and health-related risk factors for loneliness among adults aged ≥55 during the early phase of the COVID-19 pandemic in the United States, when much of the country was under shelter-in-place orders. Methods We collected data from online questionnaires in the COVID-19 Coping Study, a national stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 60 publications
4
15
0
Order By: Relevance
“…A large population-based study from the US reported that one-third of the population aged 55 and older experienced feelings of loneliness during Spring 2020. Especially persons who were not married or in a relationship commonly reported loneliness (27). Similar results have been reported from Europe in the study by Cohn-Schwartz et al (28), who found that especially older people who followed the recommendations and were physically isolated felt lonelier during the pandemic than before (28).…”
Section: Discussionsupporting
confidence: 80%
“…A large population-based study from the US reported that one-third of the population aged 55 and older experienced feelings of loneliness during Spring 2020. Especially persons who were not married or in a relationship commonly reported loneliness (27). Similar results have been reported from Europe in the study by Cohn-Schwartz et al (28), who found that especially older people who followed the recommendations and were physically isolated felt lonelier during the pandemic than before (28).…”
Section: Discussionsupporting
confidence: 80%
“…The plausible reasons for such a difference in loneliness prevalence include differences in study tools to measure loneliness, differences in the age range of participants, and online mode of survey administration. The prevalence of loneliness (52%) in the current study is similar to a previous study from the US (54%) 42 , but higher than other studies from the US 43 , the United Kingdom 44 , and Canada 15 , which reported prevalence ranging from 30 to 43%. Several factors, including study design, sampling differences, and socioeconomic contexts, may explain the variations in individuals’ loneliness during the pandemic.…”
Section: Discussionsupporting
confidence: 84%
“…The current study suggested that female participants and those living in rural areas were more likely to feel lonely than males and their urban counterparts, similar to existing literature 46 , 60 . Our finding that older adults who lived alone (without family) were more like to feel lonely is supported by 15 studies included in a review 26 and several other studies 43 , 61 , 62 . As indicated above, older individuals may live alone due to their loss of spouses and limited relationships with their family members 45 , 46 .…”
Section: Discussionsupporting
confidence: 69%
“…We examined three mental health outcomes: (1) presence of depressive symptoms evaluated with the 8-item Center for Epidemiological Studies-Depression (CES-D) scale, (2) anxiety symptoms evaluated with the 5-item Beck Anxiety Inventory (BAI), and (3) loneliness evaluated with the 3-item UCLA loneliness scale ( Fisher et al, 2005 ; Lewinsohn et al, 1997 ; O'Shea et al, 2021 ; Wilke and Straits, 2005 ). Based on previously used cut-off points, participants were considered to screen positive for symptoms of depression, anxiety, and loneliness, if they scored: ≥3 on the CES-D, ≥10 on the BAI, and ≥6 on the UCLA loneliness scale, respectively ( Kobayashi et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%